ANALISIS RESIKO SAHAM PERUSAHAAN BASIC INDUSTRY AND CHEMICALS PADA BURSA EFEK INDONESIA - Adinatan Adinatan; Khaira Amalia Fachrudin (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT   The purposes of this study were to find out and to analyze any differences of systematic risk and unsystematic risk of cement subsector ; ceramics, porcelain and glass subsector ; metal and allied products subsector ; chemicals subsector ; plastics and packaging subsector ; animal feed subsector ; wood industries subsector and ; pulp and paper subsector in Basic Industry and Chemicals’ companies that were listed in the Indonesia Stock Exchange. The types of this study were descriptive analysis and comparative analysis and the type of data used for this study were quantitative secondary data which came from Indonesia Stock Exchange’s publication about issuers’ stock data, reference books, magazines, internet, and the other scientific literatures related to this study. The methods used for collecting the data were through the documentation study from collecting the supporting data from literatures, journals and reference books to get an idea of ​​the issues, and to gather relevant secondary data from reports published by Bank Indonesia and Indonesia Stock Exchange. The methods used for data analysis were descriptive analysis, One Way Anova analysis and Independent Samples t-test analysis. The results of the first hypothesis shows that there were an average difference of systematic risk between cement subsector and those of ceramics, porcelain and glass subsector, metal and allied subsector, plastics and packaging subsector, and pulp and paper subsector. The results of the second hypothesis shows that there were no differences of unsystematic risk among all the subsectors in the Basic Industry and Chemicals’ companies.     Key Words            :     Systematic Risk, Unsystematic Risk, Stock, and Basic Industry and Chemicals